2005
DOI: 10.1007/s00586-005-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of transforaminal injections in the cervical spine evaluated by multi-slice computed tomography

Abstract: Transforaminal injections are sometimes used for the diagnosis and treatment of painful conditions in the lumbar and to a lesser degree in the cervical spine. The technique is most often used when investigating/treating radiculopathy caused by degenerative disease. But how selective are the nerve root blocks? What possible structures other than the intended nerve root are affected from such injections? This study was undertaken in order to try to answer these questions, as no study focusing on the possible spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…The correlation between lower block volume and success rate is likely related to increased diagnostic specificity and is similar to studies evaluating other diagnostic nerve blocks [28–30]. The observation that more cycles of PRF were associated with better outcomes is consistent with some [31], but not all [22], preclinical studies that found greater anti‐allodynic effects with increased PRF duration.…”
Section: Discussionsupporting
confidence: 71%
“…The correlation between lower block volume and success rate is likely related to increased diagnostic specificity and is similar to studies evaluating other diagnostic nerve blocks [28–30]. The observation that more cycles of PRF were associated with better outcomes is consistent with some [31], but not all [22], preclinical studies that found greater anti‐allodynic effects with increased PRF duration.…”
Section: Discussionsupporting
confidence: 71%
“…There are several limitations that should be addressed to place these results in context. First, although CT scans have previously been used as the definitive standard for evaluating the accuracy of fluoroscopically guided nerve blocks, 18,40 they are limited by their inability to visualize nervous tissue. Despite potential variability in nerve location, 33,41 this was deemed acceptable because the target sites are almost always the same for fluoroscopically guided MBB, [2][3][4]17,27 which are subject to the same limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five studies 28,[38][39][40][41] included in our review, three 28,39,41 were also included in the updated Datta et al review. 62 Of the remaining 13 included in the Datta et al review 62 but excluded from our study, three studies [64][65][66] were excluded as they focused on cervical spine injections (see Table 21). Six studies 27,[67][68][69][70][71] were excluded from our review because it was impossible to reconstruct sensitivity and specificity or 2 × 2 tables of index test and reference standard results.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%